SEXUAL AWARENESS AND ITS ASSOCIATION WITH HIV/AIDS PREVENTION ATTITUDES AND SEXUAL BEHAVIOR AMONG ADOLESCENTS - Devi Permata Sari; Sri Sat Titi Hamranani; Arlina Dhian Sulistyowati (Journal of Vocational Nursing, 2026)
Introduction: Adolescence is a transitional phase marked by rapid changes that are not yet matched by mature decision-making skills. Peer influence increases the likelihood of risky behaviors, including unsafe sexual practices. This is exacerbated by low levels of sexual literacy, limited awareness of reproductive health, and a lack of comprehensive sexuality education. According to a report by the United Nations Programme on HIV and AIDS (UNAIDS), approximately 1.9 million adolescent girls and young women aged 15–24 are living with HIV worldwide. This research attempts to examine sexual awareness and attitudes toward HIV/AIDS prevention and sexual behavior. Methods: The research methodology applied was a quantitative correlation study using a cross-sectional approach, involving 150 high school students in Klaten Regency, with a simple random sampling technique. The research instruments included the Sexual Awareness Questionnaire (SAQ), an HIV/AIDS prevention attitude questionnaire, and a sexual behavior questionnaire. Data analysis was performed using Kendall’s Tau test. Results: The results showed that most respondents were aged 15–18 years, with a mean age of 16.87 years. The majority were male (54.7%) and lived with their parents (97.3%). Most respondents demonstrated a moderate level of sexual awareness (72.7%), while attitudes toward HIV/ AIDS risk-reduction measures were predominantly inadequate (51.3%). Nevertheless, the majority reported engaging in safer sexual practices (91.3%). Conclusions: The results indicated no statistically significant association between sexual health awareness and attitudes toward HIV/AIDS prevention (p = 0.237). However, sexual health awareness was significantly associated with sexual behavior (p = 0.009; π = 0.209), suggesting a potential link between awareness and behavioral outcomes.